ANALISIS KOMPARATIF KONDISI EKONOMI PEDAGANG KIOS LANTAI 1 DAN PEDAGANG KIOS LANTAI 2 PASAR BESAR NGAWI PASCA REVITALISASI - Fitus Baskara; Hadi Sumarsono (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study compares the economic conditions of first and second-floor kiosk traders of Pasar Besar Ngawi after the construction and revitalization.Kiosk traders in Pasar Besar Ngawi are the primary subject of this research.For this particular research, the primary data was obtained from 78 respondents. The number of respondents has been calculated through the Slovin formula with a standard error of 10%. Furthermore, the interview method was employed to gather primary data for this research—the interviewees were chosen using a sampling technique known as disproportionate stratified random sampling.The tests used were descriptive statistics and the Mann-Whitney U test. Results show that the market has become deserted, causing many traders to experience a decrease in income and making many traders reduce working hours. A decrease in income was experienced more by traders on the second floor than traders on the first floor. Furthermore, a reduction in working hours was also experienced more by traders on the second floor than traders on the first floor. From the business certainty aspect, traders who stated they could advance were found more on the first floor than the second-floor traders. Furthermore, the results of hypothesis testing through the Mann-Whitney U test prove that there is a significant difference between the income of the first-floor traders and the income of second-floor traders, and there is a significant difference between the profits of first-floor traders and the profits of second-floor traders. The first-floor traders have higher average income than the second-floor traders;also,the first-floor traders have higher average profit than the second-floor traders.